Interpretable Machine Learning Framework for Ozone Concentration Prediction Using TAP Data and SHAP Analysis in China - Jia, Baoli; Zheng, Fayuan (Informatica, 2025)
This study aims to enhance the monitoring and prediction capabilities of ozone pollution and support precise environmental governance and improvement of atmospheric quality. It constructs and compares multiple ozone concentration prediction models, including Extreme Gradient Boosting (XGBoost), Light Gradient Boosting Machine (LightGBM), and Random Forest (RF), based on machine learning methods. The study uses national online observation data from Tracking Air Pollution in China (TAP) spanning 2015–2025, covering 34 provinces. Before modeling, the data are subjected to missing value imputation, outlier removal, and normalization. Combined with Shapley Additive Explanations (SHAP) values, the study conducts model interpretability analysis to deeply reveal the key driving factors affecting ozone formation and their regional differences. The results show that the national annual average ozone concentration increases from 105.6 μg/m³ in 2015 to 130.2 μg/m³ in 2019, with an increase of 23.3%. The peak concentration in the Beijing-Tianjin-Hebei region in 2019 reached 182.8 μg/m³, exceeding the national limit by 114%. Ozone concentration decreased in 2020 due to the impact of the epidemic, but it was still 24.6 μg/m³ higher in 2024 than in 2015. In terms of model prediction performance, XGBoost performs the best nationwide and in all major regions. At the national level, its Mean Absolute Error (MAE) is 11.3 μg/m³, Root Mean Squared Error (RMSE) is 15.6 μg/m³, R² is 0.882, and Nash-Sutcliffe Efficiency coefficient (NSE) is 0.88. SHAP analysis indicates that day of year, temperature, and sunshine duration are the main driving factors for changes in national ozone concentration. NO₂ contributes significantly in the Beijing-Tianjin-Hebei region and the Fenwei Plain, while the effects of temperature and sunshine are the strongest in the Pearl River Delta region. This study enriches the understanding of the spatiotemporal dynamics and formation mechanisms of ozone pollution, and provides solid data support and theoretical basis for the scientific formulation of regional pollution prevention and control strategies.